RELATIONSHIP BETWEEN COMPETITIVE ADVANTAGE AND VALUE CREATION AND PROFITABILITY IN THE FIRM - Orishede, Felix (African Journal of Social and Behavioural Sciences, 2021)
This study examined the impact of competitive advantage on value creation and profitability of the firm. For organizations to be successful in the current business environment it needs to have visible competitive advantages, a copy of questionnaire made up of three separate scales were used to collect data from 264 employees of Zenith Bank Plc. Three constructs of organizational resources, dynamic capabilities and distinctive competencies were used to examine competitive advantage. Simple linear regression analysis and descriptive statistical analysis used to analyze the data collected for the study. Findings revealed that significant relationships exist between organizational resources, dynamic capabilities, distinctive competencies and value creation and profitability, which means positive relationships exist between organizational resources, dynamic capabilities, distinctive competencies and value creation and profitability. The study concludes that firms could build a constant high performance when they have higher assets and competitive environments to operate. Zenith Bank Plc can rely on the resources that are worthy and erratic for a sustainable competitive advantage for high performance because such advantage can be sustained over a long period, the study recommends that managers seeking to maximize profit should first gain sustainable competitive advantage in order to stay ahead of competitors.